A sex stratified outcome analysis from the OPEN‐CTO registry. Issue 6 (19th December 2018) - Pershad, Ashish; Gulati, Martha; Karmpaliotis, Dimitrios; Moses, Jeffery; Nicholson, William J.; Nugent, Karen; Tang, Yuanyuan; Sapontis, James; Lombardi, William; Grantham, James A.; ,
Abstract: Introduction: Women have been under‐represented in trials. Due to the dearth of information about CTO‐PCI in women and discordance of previous results, sex differences in outcomes in the OPEN‐CTO Trial were investigated. Methods: OPEN‐CTO is an investigator‐initiated, multicenter, prospective observational registry of consecutive CTO patients undergoing PCI at 12 U.S. centers. The one‐year outcomes of this trial stratified by sex were examined. Optimal propensity matching was performed to compare outcomes between sexes. Multivariate conditional logistic regression modeling for predictors of procedural success was performed. Results: Women represented 19.6% of the cohort (196/1, 000 patients). Women were more likely to report dyspnea as their predominant symptom. Women reported statistically worse physical limitation and poorer quality of life as compared to men. J‐CTO scores were similar in males and females. Technical, procedural success and MACE rates were similar in both sexes. Contrast and radiation doses were however significantly lower in women. The SAQ‐ summary score, RDS, EQ‐5D VAS, PHQ‐8 scores were all improved to the same degree at 1 year in women as compared to men. Predictors of procedural success revealed that younger age, lower J‐CTO score and absence of prior CABG were predictors of procedural success. Sex did not predict procedural success or 1‐year MACE in this regression model. Conclusion: This real‐world registry revealed that women derive the same benefit from CTO‐PCI as men without additional complications and with favorable health status outcomes at 1 year. Consideration of revascularization by PCI in symptomatic women should be considered as part of the treatment when appropriate.